Piloting a National Programme for the Digitization of Medieval Manuscripts in Germany - Fabian, Claudia; Schreiber, Carolin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
An initiative to develop a concerted national programme for the digitization of medieval manuscripts in Germany was launched by five German manuscript centres in January 2013. This new proposal aims at the development of a master plan for the digitization of nearly all surviving medieval manuscripts in Germany and at the establishment of a new funding programme of the DFG (German Research Foundation), the largest research funding organization in Germany.Besides this fundamental financial aspect, other objectives are the diffusion of technical standards and know-how to less experienced cultural heritage institutions and the creation of a nationwide network of competent partners, e.g. in the areas of digitization itself, long-term storage of digital data, the administration of persistent identifiers, and the internet presentation of digital collections. An important role will be played by the German manuscripts portal, Manuscripta Mediaevalia, which is intended as the central hub for both the presentation of digital collections of German manuscripts, but also of the relevant metadata, that is, digital and ideally searchable full-text versions of scholarly, in-depth manuscript descriptions. Of course, this centralization and aggregation will also facilitate the exchange of data with other institutions.The pilot phase will lead to the definition of a national digitization strategy with a clear prioritization of projects to be approached. It also aims at the creation of a sustainable technical infrastructure for the integration of both primary and secondary digital data. In this way, the current fragmentation of information in a plethora of local digitization projects is to be superseded by a unitary and complete virtual research environment for all those interested in medieval manuscripts from Germany.